The Mediating Role of Brand Image in The Effect of Corporate Social Responsibility on Purchase Intention of Nestle Pure Life in Denpasar - Ni Putu Amrita Devi Ayudhia; I Gusti Ayu Ketut Giantari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine and explain the mediating role of brand image in the effect of corporate social responsibility (CSR) on purchase intention toward Nestle Pure Life in Denpasar. The research was conducted in Denpasar, using a sample of 100 respondents selected through purposive sampling and surveyed using offline questionnaires. The data analysis technique used in this study is path analysis with SPSS 26.0. The results indicate that all hypotheses are accepted. Corporate social responsibility has a positive and significant effect on purchase intention. Brand image also has a positive and significant effect on purchase intention. In addition, CSR significantly influences brand image. Furthermore, brand image is proven to mediate the effect of corporate social responsibility on purchase intention toward Nestle Pure Life in Denpasar. The implication of this study is the importance for Nestle Pure Life to enhance positive consumer perception through meaningful and consistent CSR programs in order to build a strong brand image that ultimately increases purchase intention among consumers in Denpasar.